Statistical parameters in planning aero-engine production - Atkinson, A. H.; Harris, J. T. (College of Aeronautics, 1963)
This report considers the estimation of statistical parameters and their application to production planning in the aero-engine industry. A similar pattern of behaviour to that already recognised as existing in the airframe industry is found to operate, though there are indications of quantitative differences. The build-up time to the planned peak rate of production in a particular situation is found to be about eighteen months but with variation between firms. The reduction in operator performance time, which occurs with repetition during the build-up period and afterwards, is discovered to be present in machining as well as assembly, but to a lesser extent. The logarithmic function generally descriptive of such a tendency is found to fit the actual man-hour content values rather than the cumulative average ones. The relationship between the logistic of output and the logarithmic function is established and made use of to estimate labour requirements from the commencement of production onwards. In addition to the above consideration of production variables, examples are given of the use of engine performance ratings to estimate costs. Finally, because of the importance of planning to productivity, a typical production programme has been included.